Rainwater harvesting practices for improving climate adaptation for farmers in Uganda - Ahamada, Zziwa (Technical Centre for Agricultural and Rural Cooperation, 2018)
Poverty and food insecurity plague many countries in sub-Saharan Africa; this includes Uganda. To increase farmer’s adaptive capacity and to increase their resilience to climate change and variability, in situ rainwater harvesting technologies and practices were promoted in the greater Masaka region, Uganda to enable farmers to sustainably produce food and generate income. This technical report presents the findings of a project aimed at documenting adoption of in situ rainwater harvesting technologies and practices by farmers to improve resilience and adaptive capacity to climate change and variability in Rakai district.